2011
DOI: 10.1039/c0cc03844j
|View full text |Cite
|
Sign up to set email alerts
|

Gold-complexes catalyzed oxidative α-cyanation of tertiary amines

Abstract: Oxidative α-cyanation of tertiary amines is catalyzed by gold complexes with trimethylsilyl cyanide to afford the corresponding α-aminonitriles in the presence of tert-butyl hydroperoxide in good to excellent yields under acid-free conditions at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(66 citation statements)
references
References 36 publications
0
62
0
4
Order By: Relevance
“…Further, these bi-functional organic compounds having adjacent functional groups show dual reactivity as the nucleophilic addition provides an easy access to various compounds such as ␣-amino aldehydes, ketones and ␤-amino alcohols [20][21][22][23][24][25]. So far a number of metal-based catalysts, such as Fe [26][27][28], Ru [29,30], V [31], Mo [32], Au [33] and Re [34] in the presence of oxidants such as molecular oxygen, hydrogen peroxide, tert-butyl hydroperoxide (TBHP) have been reported for the direct oxidative cyanation of tertiary amines. Photoredox catalysts mainly based on ruthenium have also been reported for the oxidative ␣-cyanation of sp 3 C H bonds of tertiary amines [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Further, these bi-functional organic compounds having adjacent functional groups show dual reactivity as the nucleophilic addition provides an easy access to various compounds such as ␣-amino aldehydes, ketones and ␤-amino alcohols [20][21][22][23][24][25]. So far a number of metal-based catalysts, such as Fe [26][27][28], Ru [29,30], V [31], Mo [32], Au [33] and Re [34] in the presence of oxidants such as molecular oxygen, hydrogen peroxide, tert-butyl hydroperoxide (TBHP) have been reported for the direct oxidative cyanation of tertiary amines. Photoredox catalysts mainly based on ruthenium have also been reported for the oxidative ␣-cyanation of sp 3 C H bonds of tertiary amines [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…[8] To the best of our knowledge, there is no successful example of a gold-catalyzed a-CÀH functionalization of amines using air as the sole oxidant. [5,9] Herein, we wish to report an unprecedented homogeneous gold-catalyzed amine functionalization protocol involving the oxidative C À C coupling of two different C À H bonds with air as a sustainable and efficient oxidant.…”
mentioning
confidence: 99%
“…With PIFA, increasing the time of preactivation and shorten the reaction time led to the same yield (entry 5 vs entry 2). In order to alleviate the side reaction resulted from high temperature under strongly oxidative conditions, the temperature was lowered, which as a result, delivered the same level of reactivity (entries [6][7]. It is also observed that during the reaction, unreacted substrate was not detected by TLC due to the interaction with CF 3 COOH released from PIFA.…”
Section: Resultsmentioning
confidence: 87%